The Effectiveness of CBT Group Counseling with Stress Inoculation Training and Cognitive Restructuring Techniques to Reduce Students’ Academic Stress - Ningtias, Desi Ari Shandi Ayu; Mungin Eddy Wibowo, Mungin Eddy Wibowo; Edy Purwanto, Edy Purwanto (Jurnal Bimbingan Konseling)
This study aimed to analyze CBT group counseling with stress inoculation training and cognitive restructuring techniques to reduce students? academic stress. The study used pre-test and multiple post-test design by involving 14 students of Public Senior High School 1 Semarang. Their data were collected using academic stress scale. Meanwhile, the collected data were analyzed by employing mixed ANOVA statistical test. The results showed that CBT group counseling with stress inoculation training and cognitive restructuring techniques were effective to reduce students? academic stress (F(1,12) = 22.591, p < 0.01). These findings assert that CBT group counseling with stress inoculation training and cognitive restructuring techniques is effective to reduce students? academic stress.